PHILOSOPHY AND ITS HISTORY - Mavlonova Shahzoda Turgunovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The study of philosophy and its history consists of understanding and learning the essence of this science by creating an understanding. Philosophy is a universal and universal field of science that is the basis for the development of all sciences and is fed by them, and at the same time determines the ways of their development.